Striatonigral distribution of a fluorescent reporter following intracerebral delivery of genome editors - Neuman, Samuel S.; Metzger, Jeanette M.; Bondarenko, Viktoriya; Wang, Yuyuan; Felton, Jesi; Levine, Jon E.; Saha, Krishanu; Gong, Shaoqin; Emborg, Marina E. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Targeted gene editing is proposed as a therapeutic approach for numerous disorders, including neurological diseases. As the brain is organized into neural networks, it is critical to understand how anatomically connected structures are affected by genome editing. For example, neurons in the substantia nigra pars compacta (SNpc) project to the striatum, and the striatum contains neurons that project to the substantia nigra pars reticulata (SNpr). Methods: Here, we report the effect of injecting genome editors into the striatum of Ai14 reporter mice, which have a LoxP-flanked stop cassette that prevents expression of the red fluorescent protein tdTomato. Two weeks following intracerebral delivery of either synthetic nanocapsules (NCs) containing CRISPR ribonucleoprotein targeting the tdTomato stop cassette or adeno-associated virus (AAV) vectors expressing Cre recombinase, the brains were collected, and the presence of tdTomato was assessed in both the striatum and SN. Results: TdTomato expression was observed at the injection site in both the NC- and AAV-treated groups and typically colocalized with the neuronal marker NeuN. In the SN, tdTomato-positive fibers were present in the pars reticulata, and SNpr area expressing tdTomato correlated with the size of the striatal genome edited area. Conclusion: These results demonstrate in vivo anterograde axonal transport of reporter gene protein products to the SNpr following neuronal genome editing in the striatum.